Islamic Legal Views on The Implementation of Diversion towards Children Involved in Narcotics Crimes - Farid Nur Mustaqim; M. Junaidi (Proceeding International Conference Restructuring and Transforming Law, 2026)
The abuse of narcotics involving children has become a very serious issue, as it affects their physical and mental development as well as their future. Within the juvenile criminal justice system in Indonesia, diversion is used as an effort to resolve cases outside the court through a restorative justice approach. This study aims to examine the perspective of Islamic law on the implementation of diversion for children involved in narcotics-related crimes. The research employs a normative juridical method with statutory and conceptual approaches. Data were obtained through literature study, including primary legal materials such as legislation, the Qur'an, and Hadith, as well as secondary legal materials such as books, scientific journals, and expert opinions. The novelty of this research lies in the analysis of the relationship between the concept of diversion in the juvenile criminal justice system and the principles of Islamic law, particularly the concepts of maqashid al-sharia, islah, and musyawarah in handling children involved in narcotics crimes. The results show that, from the perspective of Islamic law, children are regarded as a trust (amanah) that must be protected and nurtured. Diversion is understood as a form of resolution that aligns with the principles of islah and musyawarah, which emphasize peace, restoration of social relationships, and opportunities for children to improve themselves. In practice, the implementation of diversion involves law enforcement officers, families, communities, and social institutions through a deliberation process that results in agreements in the form of rehabilitation, guidance, and social reintegration of the child. The implementation of diversion for children involved in narcotics crimes is in line with the values of Islamic law, which emphasize protection, guidance, and rehabilitation of children in order to achieve restorative justice and a better future for them.